2001
DOI: 10.1183/09031936.01.00106201
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility locus genetic markers of beryllium sensitization and disease

Abstract: Hypersensitivity to beryllium (Be) is found in 1–16% of exposed workers undergoing immunological screening for beryllium disease using the beryllium lymphocyte proliferation test (BeLPT). However, only ∼50% of BeLPT-positive workers present with lung granulomas (i.e.berylliosis). As berylliosis is associated with the human leukocyte antigen (HLA)-DP supratypic marker DPGlu69, the authors asked whether this marker is differentially associated with disease presentation.A population of 639 workers from a berylliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
116
3
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(127 citation statements)
references
References 32 publications
7
116
3
1
Order By: Relevance
“…HLA-DPB1*E69 and BeS. However, elimination of the BeS data reported by Saltini et al (2001) from our analyses did not change the overall ranking. All of the reports described were case-control studies, and we remain ignorant of many facets of the natural history of CBD, especially as it pertains to the progression from BeS to disease.…”
Section: Discussioncontrasting
confidence: 44%
See 3 more Smart Citations
“…HLA-DPB1*E69 and BeS. However, elimination of the BeS data reported by Saltini et al (2001) from our analyses did not change the overall ranking. All of the reports described were case-control studies, and we remain ignorant of many facets of the natural history of CBD, especially as it pertains to the progression from BeS to disease.…”
Section: Discussioncontrasting
confidence: 44%
“…Moreover, we are unaware of the impact of any potential allele misclassification, which is suggested by the growing numbers of haplotypes reported since 1999. Regarding the ranking of alleles with respect to BeS (Table 1), we considered the possibility of bias, potentially introduced by the data reported by Saltini et al (2001), as, unlike those of Wang et al (2001) and Rossman et al (2002), these data did not show an association between inheritance of kT/e, respectively. The solvent-accessible surface is displayed in white.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Richeldi et al (36) have reported an 85-fold (95% CI 10.9-3578.0) risk of chronic beryllium disease for workers with an HLA-DPB1 coding for glutamic acid (Glu-69) in the 69th position. Subsequent studies confirmed this relationship (37)(38)(39); however, the risk ratios were lower. The question in this scenario is whether prospective employees in a beryllium manufacturing plant should be screened for Glu 69 variant prior to employment.…”
Section: Ethylene Oxide and Glutathione-s-transferase Thetamentioning
confidence: 48%